Bad Brains: Crime and Drug Abuse from a Neurocriminological Perspective - Jorgensen, Cody (American journal of criminal justice, 2016)
Research into the biosocial correlates of antisocial behavior has revealed the importance of integrating sociological findings with evidence flowing from genetics and neuroscience. The present study represents a step toward such integration by offering an in-depth overview of neurocriminology, which is the study of the brain and how it affects antisocial behavior. We consider the role of the brain in both antisocial/criminal behavior as well as in drug use/abuse. We highlight various regions/systems in the brain that have been identified as targets for intervention and as areas in need of more study. This knowledge equips us with the foundation to think translationally about how to promote mental health, adaptive behavior, and well-being among drug using criminal offenders.